2001
DOI: 10.1590/s0103-31312001000200001
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in goiabeira serrana: genotype response, auxinic shock and synthetic seeds

Abstract: The induction and control of in vitro somatic embryogenesis is dependent of a number of factors. The genotype of the mother plant donor of explants and the kind of auxin play essential roles in conferring embryogenic competence. Once obtained somatic embryos may be encapsulated in alginate originating synthetic seeds that can be stored at low temperatures. Considering this the present work aimed at the assessment of five different genotypes, five periods of 2,4-D shock (20 muM for 1, 2, 4, 8 and 16 weeks) (), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
0
19
0
5
Order By: Relevance
“…Resultados prévios mostraram que o cultivo in vitro de embriões zigóticos de Acca sellowiana tratados com 2,4-D de forma contínua ou transitória induzia a formação e o desenvolvimento de embriões somáticos, enquanto que na ausência desse regulador ocorria apenas a germinação das sementes e o crescimento inicial das plântulas (Guerra et al 1997). A importância dessa auxina na indução da embriogênese somática de A. sellowiana foi posteriormente confirmada por Guerra et al (2001).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Resultados prévios mostraram que o cultivo in vitro de embriões zigóticos de Acca sellowiana tratados com 2,4-D de forma contínua ou transitória induzia a formação e o desenvolvimento de embriões somáticos, enquanto que na ausência desse regulador ocorria apenas a germinação das sementes e o crescimento inicial das plântulas (Guerra et al 1997). A importância dessa auxina na indução da embriogênese somática de A. sellowiana foi posteriormente confirmada por Guerra et al (2001).…”
Section: Resultsunclassified
“…A rota da embriogênese somática desta espécie foi inicialmente estabelecida por Cruz et al (1990) e o efeito da composição de açúcares do meio (Canhoto & Cruz 1994), de fatores hormonais (Guerra et al 2001), da influência do genótipo (Guerra et al 1997) e uma análise histoquímica minuciosa (Cangahuala-Inocente et al 2004), bem como a descrição de anomalias nos embriões somáticos (Pescador et al 2008a) já foram relatadas. Contudo, os processos fisiológicos da rota completa da embriogênese nessa espécie ainda não são suficientemente conhecidos, de forma a permitir o sucesso na obtenção de plântulas normais a partir da embriogênese somática.…”
Section: Introductionunclassified
“…Dal showed that different nitrogen sources in the culture medium affected the number of somatic embryos developed from zygotic embryos. Guerra et al (2001) demonstrated that somatic embryogenesis in this species was affected by 2,4-D pulses, and histological studies revealed abnormalities on the development of somatic embryos. Stefanello et al (2005) reported embryogenic competence from floral tissues, and Cangahula-Inocente et al (2007) included the technology of synthetic seeds in the somatic embryogenesis protocol.…”
Section: Introductionmentioning
confidence: 90%
“…Aspectos embriológicos de Acca sellowiana já foram estudados, especialmente a embriogênese somática (Canhoto & Cruz, 1996a, b;Guerra et al, 1997;Guerra et al, 2001;Pescador, 2004). Por outro lado, com exceção dos trabalhos de Polunina (1957;1963), a embriogênese zigótica foi pouco estudada.…”
Section: Introductionunclassified